Abhạ̄th al-Muʼtamar al-Thālith lil-Dirāsāt al-ʻUthmānīyah fī Misṛ - Crecelius, Daniel.; Ismāʻīl, Muḥammad Ḥusām al-Dīn. (Dār al-Āfāq al-ʻArabīyah, 2004)
Egypt; history; architecture, Islamic; Ottoman era; congresses; papers from the Third Conference for Ottoman Studies in Egypt.